Do children with Dravet syndrome continue to benefit from stiripentol for long through adulthood?. (22nd August 2018) - Chiron, Catherine; Helias, Marie; Kaminska, Anna; Laroche, Cecile; de Toffol, Bertrand; Dulac, Olivier; Nabbout, Rima; An, Isabelle
Summary: Objective: To evaluate continuing stiripentol treatment in adulthood in Dravet syndrome (DS). Method: Longitudinal data were collected from the last visit prior to age 15 years (V15 y ) to the last visit in adulthood (Vadult ) in the 40 DS patients (32 typical, eight atypical) of a French historical cohort (Paris) of subjects who continued stiripentol from childhood or adolescence to adulthood. Results: At Vadult (18‐40 years, median = 23 years), all the patients were still receiving stiripentol (exposure = 3‐24 years, median = 18 years), associated with clobazam (40/40), valproate (39/40), and topiramate (21/40). Between V15 y and Vadult, stiripentol was interrupted in five patients (two for adverse events) but reintroduced following seizure aggravation. Loss of appetite affected 15 of 40 patients but resolved after reducing the dose of stiripentol or valproate; no other new stiripentol‐related adverse events were reported. Mean stiripentol dose was progressively decreased from 39 to 25 mg/kg/d ( P  = 0.0002), whereas clobazam (0.27 mg/kg/d) and valproate (14 mg/kg/d) remained stable. At Vadult, 37 of 40 patients still had generalized tonic–clonic seizures, but none still had status epilepticus (vs three at V15 y ) and only one had myoclonia. During adulthood, generalized tonic–clonic seizure frequency and duration continued to decrease ( P  = 0.02, P  = 0.008) and 10 patients experienced seizure‐free periods ≥ 1 years (up to 5 years). All patients already had intellectual disability at V15 y, but retardation was more severe at Vadult ( P  = 0.03). Furthermore, neurological/gait condition had declined (two patients became bedridden) and behavior had worsened ( P  < 0.0002). Nevertheless, the 33 patients on stiripentol from infancy/childhood (<15 years) tended to have better seizure outcome in midadulthood than the seven treated from adolescence (>15 years) and the DS patients treated from adult age or stiripentol‐naive subjects reported in the literature. Significance: The efficacy and safety of the stiripentol/valproate/clobazam combination started at pediatric age are maintained at very long term during adulthood. Such prolonged stiripentol therapy tends to positively impact the late prognosis of epilepsy, especially when initiated before adolescence.